Needle-based confocal laser endomicroscopy in the diagnosis of peripheral pulmonary nodule: a preliminary report - Su, Zhuquan; Zhong, Changhao; Li, Shiyue; Chen, Xiaobo; Chen, Yu; Tang, Chunli (Journal of Thoracic Disease, 2017)
Lung cancer is one of the most fatal cancers in the world. To early distinguish benign and malignant pulmonary nodule is critical for disease prognosis. Confocal laser endomicroscopy (CLE) can be used to explore bronchus mucous membrane, alveolar elastic fiber structures and microvessels, and could be helpful for the diagnostic imaging and for the localization guidance. In this report, we presented two cases of peripheral pulmonary nodule. Under the guidance of X-ray and endobronchial ultrasound, needle-based confocal laser endomicroscopy (nCLE) could directly approach the peripheral pulmonary nodule via an exploratory puncture needle. The results indicated that the utility of the nCLE is helpful to precise positioning and characterize the peripheral pulmonary nodule. This report presents for the first time the application of nCLE for positioning the peripheral extraluminal nodule and describe the different confocal imaging features between adenocarcinoma and tuberculosis.